1984
DOI: 10.1021/bi00299a001
|View full text |Cite
|
Sign up to set email alerts
|

Active site of C3a anaphylatoxin: contributions of the lipophilic and orienting residues

Abstract: Activation of the serum complement cascade generates C3a anaphylatoxin, a primary mediator of inflammation. The active-site pentapeptide from the COOH terminus of C3a, Leu-Gly-Leu-Ala-Arg (residues 73-77), exhibits the inflammatory activities and specificity of the native 77-residue polypeptide. Functionally important features of this active site were studied by testing the ability of 22 synthetic analogues of this pentapeptide to contract isolated muscle strips from guinea pig ileum and to desensitize this ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…In particular, knowledge of the crystal structure of C3a (34) facilitated accurate modeling of the C5a protein (26), and NMR studies have confirmed that the structures in solution of C3a (35) and C5a (24) are highly similar. Examination of C3a structure-activity relationships via synthesis of peptides mimicking the carboxyl terminus has demonstrated the crucial importance of this region for C3a activity (36)(37)(38). However, C3a distinctly differs from C5a in that a synthetic carboxyl-terminal peptide of 21 residues was found to account for essentially the full biologic potency of the C3a molecule (38).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, knowledge of the crystal structure of C3a (34) facilitated accurate modeling of the C5a protein (26), and NMR studies have confirmed that the structures in solution of C3a (35) and C5a (24) are highly similar. Examination of C3a structure-activity relationships via synthesis of peptides mimicking the carboxyl terminus has demonstrated the crucial importance of this region for C3a activity (36)(37)(38). However, C3a distinctly differs from C5a in that a synthetic carboxyl-terminal peptide of 21 residues was found to account for essentially the full biologic potency of the C3a molecule (38).…”
Section: Resultsmentioning
confidence: 99%
“…Removal of Arg77 from the C-terminal end of C3a abolishes C3aR affinity and most biologic activities, and substitution with Lys77 gave at least 300 times less activity. Blockage with amide on carboxyl group of Arg77 in C3a was at least 1,000 times less active~Caporale et Erickson et al, 1981;Unson et al, 1984!. Therefore, we selected charged residues in C3aR as candidates for site-directed mutagenesis as a means to define the primary determinants involved in C3a binding.…”
Section: Discussionmentioning
confidence: 99%
“…in the peptide sequences [32,33]. The con formation of active peptides were altered by residue replacements [34,35] in an attempt to understand structure-function relation ships as they pertain to the C3a molecule.…”
Section: Fragment C-n-y-i-t-e-l-r-r-q-h-a-r-a-s-h-l-g-l-a-r (C3a 57-7mentioning
confidence: 99%